An article Immunohistochemical Expression of Ki 67 &CD31 in Iraqi patients with Astrocytomas ,A clinicopathological Studies. - Almukhtar, Zainab Khalid (Karbala Journal of Medicine, 2019)
Abstract: Introduction : Astrocytomas are the most common primary tumor of the central nervous system,the distinction between them relies mainly on both genetic and histological criteria. However, diagnosis absolutely based on histology has a high interobserver variations and remains problematic even for an experienced neurological pathologist. The objective of this study: To assess the immunohistochemical expression of Ki67 as proliferative markers to study proliferative activity and CD31 as an endothelial cell marker for the sake of studying vascular proliferation in astrocytomas interrelated with some clinicopathological parameters (age, gender, site of the tumor, and tumor grade) in Iraqi patients, will aid in identifying the prognosis for patients with neoplasms. Materials and methods: In this retrospective study covering the period from January 2016 to November 2017 , 41 formaline –fixed paraffin –embedded tissue blocks represent cases of surgically removed Astrocytomas were retrieved from the archived materials in specialized surgical hospital. The histopathologic diagnosis had been revised and all cases were stained by immunohistochemical technique with Ki 67 & CD 31 antibodies and assessed independently by three pathologists. Values were considered statistically significant when p<0.05. Results: Fibrillary astrocytoma (WHO grade II) was found to be the most common type among astrocytic tumors with the peak age incidence of astrocytomas found in the second and sixth decades of life, and a slight male predominance had been identified. Parietal location of tumor consider most common site ,There was a significant correlation between the age of the patients and the grade of the tumor on one side & Ki-67 labeling indix, and microvessel density (MVD) detected by CD31 on other side (p<0.05). While no significant correlation with the site and gender. Conclusion: A significant correlation was found between Ki67 labeling indices, and MVD (microvessel density) detected by CD31, and between the clinicopathological variables of astrocytomas (age and grade of tumor), Consequently Ki-67 as markers for proliferation, and MVD as a marker of angiogenesis, could be used as ancillary methods in the differentiation of borderline grades of astrocytomas & help in prediction the prognosis of astrocytic tumors especilally in centers where there are difficulty in providing the molecular analysis . Keywords: Astrocytoma, immunohistochemistry Ki‑67, immunohistochemistry CD 31.